Resting-State Functional MRI of Healthy Adults: Temporal Dynamic Brain Coactivation Patterns - Li, Jia; Fu, Shuai; Gong, Ze; Zhu, Zhaohua; Zeng, Dong; Cao, Peihua; Lin, Ting; Chen, Tianyu; Wang, Xiaoshuai; Lartey, Richard; Kwoh, C. Kent; Guermazi, Ali; et al. (Radiology, 2022)
Background: The aging brain is typically associated with aberrant interactions of large-scale intrinsic networks. However, the dynamic variation of these networks' coactivation or deactivation across the adult lifespan remains unclear.
CRIS-Team WoS Importer:2022-09-09